P232 Assessing effectiveness and patient perceptions of a novel electronic medical record for the management of inflammatory bowel disease. (27th May 2021) - Kaazan, P; Li, T; Seow, W; Bednarz, J; Pipicella, J; Ng, W; Wiiliams, A J; Connor, S; Andrews, J
Abstract: Background: There is an increasing prevalence of chronic disease worldwide, resulting in multiple management challenges. Inflammatory bowel disease (IBD) is an exemplar chronic disease requiring optimal longitudinal coordinated care. We propose that Crohn's Colitis Care (CCCare), a novel IBD-specific electronic medical record intended to improve IBD care is effective and acceptable to patients. We aimed to assess both the effectiveness of CCCare for data capture and patients' acceptability of CCCare. Methods: Methods: The study was conducted at two tertiary Australian hospitals with dedicated IBD services: Royal Adelaide Hospital and Liverpool Hospital. The effectiveness of CCCare was examined by comparing IBD-specific data completeness between pre-existing medical records and CCCare. Acceptability was assessed with quantitative and qualitative feedback through the CCCare patient portal and with standardized paper-based questionnaires administered to a convenience sample of IBD clinic patients in two unmatched pre-CCCare and post-CCCare exposure cohorts. Descriptive statistics and multivariable regression models were applied to specifically examine overall ratings of CCCare acceptability using a 10-point numeric scale; factors associated with acceptability before exposure to the system and whether exposure or security concerns influenced its acceptability. Results: In all 73 cases reviewed, there was data gain when using structured CCCare fields compared to IBD documentation in usual medical records. Acceptability assessment through the patient portal feedback of 287 patients showed that the majority were very likely to recommend it to others (score, 8.56 ± 2.2 on a scale of 0–10). Common themes of concern among the 22 respondents with qualitative feedback were related to the novelty and limited experience of CCCare. Study questionnaires indicated that the overall acceptability in the combined cohort (n=310) was very high (8.4 ± 2.1; scale of zero to ten) with more than three-quarters of patients rating acceptability as at least 8 out of 10. Self-reported information technology (IT) literacy was positively associated with acceptability. Exposure had a small positive affect on acceptability while the level security concerns had little impact on acceptability. Conclusion: The IBD-specific electronic medical record CCCare is effective in facilitating enhanced completeness of IBD-specific data capture in comparison to pre-existing medical records. It is highly acceptable to patients, especially those with reasonable IT literacy. Patient concerns about privacy and security of EMRs did not significantly influence acceptability.